Ð”ÐµÐ¹ÑÑ‚Ð²Ð¸Ðµ Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ñ‹Ñ… Ñ‚ÐºÐ°Ð½ÐµÐ¹ Ð½Ð° Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ð¸Ð·Ð¼ Ð»Ð¸Ð¿Ð¸Ð´Ð¾Ð² Ð¿Ñ€Ð¸ Ð³Ð¸Ð¿Ð¾Ñ‚Ð¸Ñ€ÐµÐ¾Ð·Ðµ Ð² ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ðµ - Chuykova, V. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The effect of introduction of human fetal thyroid gland fragment, allogenic placenta and combined introduction of human xenogenic fetal thyroid gland and allogenic placenta on lipid metabolism under experimental hypothyrosis has been investigated. The data obtained enable to conclude about the application efficiency of embryofetoplacental complex products for lipid spectrum normalisation under thyroid gland hypofunctions.